2023
DOI: 10.3390/jof9090892
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Climate Niche of Sclerotinia sclerotiorum Using Maximum Entropy Modeling

Susan D. Cohen

Abstract: Sclerotinia sclerotiorum, a fungal pathogen, causes world-wide crop losses and additional disease management strategies are needed. Modeling the climate niche of this fungus may offer a tool for the selection of biological control organisms and cultural methods of control. Maxent, a modeling technique, was used to characterize the climate niche for the fungus. The technique requires disease occurrence data, bioclimatic data layers, and geospatial analysis. A cross-correlation was performed with ArcGIS 10.8.1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…these models due to its superior predictive performance [5,45,46]. It is effective even when few occurrence records are known and the association between climatic and environmental elements is unpredictable [6,44,47].…”
Section: Occurrence Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…these models due to its superior predictive performance [5,45,46]. It is effective even when few occurrence records are known and the association between climatic and environmental elements is unpredictable [6,44,47].…”
Section: Occurrence Recordsmentioning
confidence: 99%
“…Currently, niche models like the Maxent (Maximum Entropy) model [37], ENFA (Ecological Niche Factor Analysis) model [38], CLIMEX (Climate Change Experiment) [39], and GARP (Genetic Algorithm for Rule-set Production) model [40] and GLMs (Generalized Linear Models) [41] are widely used to simulate and predict the appropriate areas of fungal diseases [5,[42][43][44]. The Maxent modeling approach is widely utilized among these models due to its superior predictive performance [5,45,46]. It is effective even when few occurrence records are known and the association between climatic and environmental elements is unpredictable [6,44,47].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that S. sclerotiorum can also grow endophytically in monocots, including rice, wheat, maize, barley, and oat [4][5][6]. Based on infected host plant species, bioclimatic data, and geographic locations, economic losses caused by S. sclerotiorum are substantial and can vary extremely [7,8].…”
Section: Introductionmentioning
confidence: 99%